Gir Lion Census, 1968 - Dalvi, M. K. (Indian Forester, 1969)
The fifth Lion Census was conducted in the Gir forest of Gujarat State in May-june 1968. Gir forest is the only home of the Asian Lion and to get an accurate estimate of its population it was suggested in the past that census of this animal should be taken every five years. Consequently the 1968 census was carried out between May 27th, 1968 and June 7th, 1968. The prominent feature of this census is that in addition to the usual method of pug mark count, a visual count of animals was taken by actually congregating and temporarily localising the animals on live baits fixed up at various centres in the census area. It is emphasised that the visual count method is adopted for the first time in history of Lion census in the Gir forest. The article deals with the history of lion, its present habitat and its population.